PENGARUH PENINGKATAN LAJU ENDAP DARAH TERHADAP HASIL PEMERIKSAAN FERITIN SERUM PADA IBU HAMIL - gilang nugraha; Nur Masruroh (UNUSA Press, 2019)
Serum ferritin (SF) examination is a test parameter used to assess iron deposits in the body. SF examination has limitations, the degree is influenced by inflammation because ferritin is an acute phase protein. Elevated SF levels follow the increase in other acute phase proteins, the acute phase proteins of the gamma-globulin group to increase Erythrocyte Sedimentation Rate (ESR), as the proteins neutralize the membrane of the negatively charged erythrocytes Thus accelerating the ESR. Enhanced ESR can also be found in pregnant women, the increase in such ESR occurs during pregnancy. This research aims to determine whether there is an increase in ESR relation to SF examination results in pregnant women. The study used Cross sectional studies conducted in Puskesmas Jagir, Wonokromo, Surabaya City which was conducted in May 2019, with the samples of pregnant women research. Blood sampling is 6 mL and is accommodated as much as 3mL on purple tubes for ESR inspection and 3mL on red tubes for SF examination. Laboratory test results are conducted in correlation tests. A total of 30 pregnant women respondents participated in the study, an average age of 27 years and an average gestational age of 34 weeks. ESR inspection results are 56 mm/hr (range: 27 – 117 mm/hr) and SF 20 ng/mL test result (range: 2 – 149 ng/mL). The correlation test result indicates that there is no increase in the ESR value of the SF level (P = 0.240). It was concluded that the increase in ESR in pregnant women did not affect the results of SF examinations, increased due to hemodilution due to the physiological factor of pregnancy, resulting in decreased blood viscosity and increased blood erythrocyte sedimentation rate.